Visual pollution : concepts, practices and management framework - Nawaz, Raheel; Wakil, Khydija (Emerald points., 2022)
Visual pollution is an emerging, multi-dimensional, subjective, and under studied area of manmade environments that has recently received researchers' focus. Visual Pollution: Concepts, Practices and Management Framework offers the first substantial cutting-edge exploration of visual pollution in urban settlements, uncovering the conceptualisation, geography-specific visual pollutants, methods of visual pollution assessment and management frameworks. Nawaz and Wakil dive into the contrasting prevalence of visual pollution geographically and the connection of human behaviour with urban aesthetics, urban management, measurement tools, information systems and regulatory frameworks. This novel contribution fills the international knowledge gap to generate dynamic and practical solutions for the mitigation in regulatory and enforcement frames. Providing a holistic picture to a diverse multi-dimensional readership interested to explore the phenomena of visual pollution, Visual Pollution: Concepts, Practices and Management Framework is an essential read for those working and researching in the fields of urban design, property management, planning, building, and policymakers confronted with a rapidly urbanising planet.